Implementasi Fungsi Manajemen dalam Proses Bongkar Muat PT. PBM Adipurusa - Erma Widyastuti; Rahmawati Riantisari (Universitas Muhammadiyah Klaten, 2024)
Maritime transportation is the backbone of the transportation system of all archipelagic countries such as Indonesia, therefore ports play a very important and strategic role. One of the functions of the port is as a transportation chain or meeting point for transportation modes which are actually played by the terminal. Daily activities in a loading and unloading company certainly require a chart or framework that contains the flow of activities including planning, organizing, mobilizing and evaluating. Seeing the urgency of the importance of managing management functions in organizations, it is necessary to study more deeply how management functions are managed in loading and unloading companies. Qualitative research method with descriptive analysis. Therefore, planning begins before the ship arrives, preparing loading and unloading equipment, operational planning meetings, permit applications, equipment preparation and field preparation. Organizing is done by managing the human resources available in the company. The implementation includes activities for handling container unloading and handling container cargo. Control is carried out by making reports which include operations per shift and reports on the realization of demolition. In conclusion, the management function carried out by PT. PBM Adipurusa has been running well.